Why Is The Evolution of Urban-Rural Wage Disparities in Bangladesh Slow - Rahman, Md Aminur (International Journal of Accounting and Economics Studies, 2025)
Instead of studying at a static point, this article has studied the dynamics of urban-rural wage disparities in Bangladesh by analyzing cross-sectional data derived from the labor force survey conducted during two distinct periods. The study utilizes the Juhn–Murphy–Pierce (JMP) decomposition method and extends it by adding propensity score matching (PSM) to derive empirical results. Moreover, the bootstrapping method determined the significance level of the empirical result. The findings of the study demonstrate that the pace of the reduction of the wage gap is impeded, mainly due to human capital and urban-centric industries. Based on the findings, it is recommended to prioritize investments in education and skills development and make policies to attract educated and skilled labor in rural areas. This paper provides informative details about the wage disparities between urban and rural areas in Bangladesh, which could be advantageous for academicians, researchers, planners, and policymakers.
Keywords: Bangladesh, Dynamic decomposition, regional wage differentials, Labor economics, Urban-rural wage gap